The evolution of the writing artist : from a portrait of the artist as A Young Man to Midnight’s Children and in the Light of What We Know - Shoily, Kazi Farzana (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2015.